Risk of chronic arthralgia and impact of pain on daily activities in a cohort of patients with chikungunya virus infection from Brazil - Silva, Monaíse M. O. (2021)
Objectives: To investigate risk factors for persistent arthralgia in patients with chikungunya, and describe its impact on daily activities. Methods: From September 2014 to July 2016, a surveillance study enrolled patients with acute febrile illness in Salvador, Brazil, and detected those with chikungunya virus infection using IgM enzyme-linked immunosorbent assay or reverse transcriptase polymerase chain reaction. Telephone follow-ups were performed to ascertain the progression of disease. Results: Of 153 followed cases, 65 (42.5%) reported chronic arthralgia that lasted >3 months, and 47 (30.7%) were still symptomatic at the time of the interview (approximately 1.5 years after symptom onset). Limitations in daily activities and mental distress were reported by 93.8% and 61.5% of those with chronic arthralgia, respectively. Female sex [risk ratio (RR) 1.79, 95% confidence interval (CI) 1.95–2.69] and age (RR 1.02 for each 1-year increase, 95% CI 1.01–1.03) were independent risk factors for chronic arthralgia. Chronic arthralgia was not associated with co-infection with dengue virus (RR 0.97, 95% CI 0.48–1.94) or chikungunya viral load at diagnosis (median chikungunya virus RNA of 5.60 and 5.52 log10 copies/μL for those with and without chronic arthralgia, respectively; P = 0.75). Conclusions: These findings reinforce the high frequency of chronic chikungunya arthralgia, and highlight the substantial disability associated with the persistence of pain. Development of novel strategies to mitigate the transmission of chikungunya virus and to provide long-term medical assistance for patients with chikungunya are needed urgently.